Coordination chemistry of organotin (IV) complexes with ono-donor ligands - Mayuran, Perumal (Universiti Malaysia Sarawak, UNIMAS, 2009)
Three organotin(IV) complexes of salicylaldehyde furoic acid hydrazone ligand (1) with RnSnCl4-n (n = 2, 3) have been synthesized in the presence of base in absolute methanol in 1:2:1 mole ratio (metal:base:ligand). Two organotin(IV) complexes of ligand (1) have also been synthesized in the presence of base in absolute methanol in 1:1:1 mole ratio (metal:base:ligand). Another three organotin(IV) complexes of 2-hydroxyacetophenone furoic acid hydrazone ligand (2) in 1:2:1 mole ratio (metal:base:ligand) have been synthesized using the same method. All organotin(IV) complexes (3-10) have been characterized by CHN analyses, UV-Visible and FTIR spectral analyses. Among them, ligand (2) and its organotin(IV) complex have also been studied by 1H NMR spectra. Spectral studies suggested that both the ligands (1-2) act as dinegative tridentate chelating agents in all the organotin(IV) complexes (3-10). Organotin(IV) complexes (3-5, 8-10) are non electrolytic in nature and are proposed to have five coordinated molecular geometry around the central tin(IV) atom whereas for the organotin(IV) complexes (6-7), they are electrolytic in nature and are proposed to have six coordinated molecular geometry around the central tin(IV) atom, respectively.